The DnaJ-Like Zinc Finger Domain Protein PSA2 Affects Light Acclimation and Chloroplast Development in Arabidopsis thaliana - Wang, Yan-Wen; Chen, Si-Ming; Wang, Wei-Jie; Huang, Xing-Qi; Zhou, Chang-Fang; Zhuang, Zhong; Lu, Shan (Frontiers in Plant Science, 2016)
The biosynthesis of chlorophylls and carotenoids and the assembly of thylakoid membranes are critical for the photoautotrophic growth of plants. Different factors are involved in these two processes. In recent years, members of the DnaJ-like zinc finger domain proteins have been found to take part in the biogenesis and/or the maintenance of plastids. One member of this family of proteins, PSA2, was recently found to localize to the thylakoid lumen and regulate the accumulation of photosystem I. In this study, we report that the silencing of PSA2 in Arabidopsis thaliana resulted in variegated leaves and retarded growth. Although both chlorophylls and total carotenoids decreased in the psa2 mutant, violaxanthin and zeaxanthin accumulated in the mutant seedlings grown under growth condition. Lower levels of non-photochemical quenching and electron transport rate were also found in the psa2 mutant seedlings under growth condition compared with those of the wild-type plants, indicating an impaired capability to acclimate to normal light irradiance when PSA2 was silenced. Moreover, we also observed an abnormal assembly of grana thylakoids and poorly developed stroma thylakoids in psa2 chloroplasts. Taken together, our results demonstrate that PSA2 is a member of the DnaJ-like zinc finger domain protein family that affects light acclimation and chloroplast development.